2022
DOI: 10.1186/s12916-022-02363-8
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive and integrative analyses identify TYW5 as a schizophrenia risk gene

Abstract: Background Identifying the causal genes at the risk loci and elucidating their roles in schizophrenia (SCZ) pathogenesis remain significant challenges. To explore risk variants associated with gene expression in the human brain and to identify genes whose expression change may contribute to the susceptibility of SCZ, here we report a comprehensive integrative study on SCZ. Methods We systematically integrated the genetic associations from a large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…TYW5 (tRNA-YW synthesizing protein 5) encodes protein TYW5, a tRNA hydroxylase that is involved in epigenetic modification in the brain, 40 and has been reported highly expressed in the dorsolateral prefrontal cortex in patients with schizophrenia as a risk gene of schizophrenia, which is related to a higher risk of AD. 41 In addition, a genome-wide association study study reported the associations between an SNP in TYW5 and sleep apnea. 42 Because sleep apnea has been reported to be related to tau aggregation in preclinical and prodromal stages of AD, 43 we hypothesize that the significant associations between TYW5 and tau pathology in women in this study might be related to sleep apnea, which suggests a potential avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…TYW5 (tRNA-YW synthesizing protein 5) encodes protein TYW5, a tRNA hydroxylase that is involved in epigenetic modification in the brain, 40 and has been reported highly expressed in the dorsolateral prefrontal cortex in patients with schizophrenia as a risk gene of schizophrenia, which is related to a higher risk of AD. 41 In addition, a genome-wide association study study reported the associations between an SNP in TYW5 and sleep apnea. 42 Because sleep apnea has been reported to be related to tau aggregation in preclinical and prodromal stages of AD, 43 we hypothesize that the significant associations between TYW5 and tau pathology in women in this study might be related to sleep apnea, which suggests a potential avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…TYW5 is involved in the carbon hydroxylation of wybutosine (yW), a hypermodified guanosine nucleoside that is essential for correct phenylalanine codon translation [41], into hydroxywybutosine (OHyW) in tRNA (Phe) [134]. While the regulatory functions of its action have not been dissected, TYW5 has been recently identified as a schizophrenia risk gene [135]. Again, the biological functions of this protein should be more deeply examined.…”
Section: Tyw5mentioning
confidence: 99%
“…The eQTL SNPs can play critical roles in complex trait phenotypes. Indeed, studies of psychiatric disorders integrating GWAS and eQTLs have successfully identified novel genetic loci that were not detected with GWAS alone (e.g., major depressive disorder (MDD) and schizophrenia) [ 20 , 24 28 ]. Additionally, a recent study showed psychiatric disorders-related genetic variants are enriched at regulatory regions (e.g., histone modifications, DNA accessibility, and enhancer-promoter interaction regions affecting gene expression) [ 29 ] Although genomic studies integrating eQTLs in regulatory regions have been performed for several psychiatric disorders, to the best of our knowledge, this approach has not been taken for suicide death.…”
Section: Introductionmentioning
confidence: 99%